2013
DOI: 10.1021/jp4076806
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of the OH + Glyoxal Reaction: Experimental Evidence and Quantification of Direct OH Recycling

Abstract: The kinetics of the OH + glyoxal, (HCO)2, reaction have been studied in N2 and N2/O2 bath gas from 5-80 Torr total pressure and 212-295 K, by monitoring the OH decay via laser induced fluorescence (LIF) in excess (HCO)2. The following rate coefficients, kOH+(HCO)2 = (9.7 ± 1.2), (12.2 ± 1.6), and (15.4 ± 2.0) × 10(-12) cm(3) molecule(-1) s(-1) (where errors represent a combination of statistical errors at the 2σ level and estimates of systematic errors) were measured in nitrogen at temperatures of 295, 250, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 57 publications
(104 reference statements)
4
37
0
Order By: Relevance
“…The IR and UV spectra of carbon suboxide were measured, showing good agreement with earlier work (Bayes, 1961;Long et al, 1954;Miller and Fateley, 1964;Vander Auwera et al, 1991). The atmospheric photolysis rate constants obtained from the UV spectrum and assuming a photo-dissociation quantum yield of unity range from 1 × 10 −6 to 4.0 × 10 −6 s −1 , depending on the altitude, for a zenith angle of 50 • .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The IR and UV spectra of carbon suboxide were measured, showing good agreement with earlier work (Bayes, 1961;Long et al, 1954;Miller and Fateley, 1964;Vander Auwera et al, 1991). The atmospheric photolysis rate constants obtained from the UV spectrum and assuming a photo-dissociation quantum yield of unity range from 1 × 10 −6 to 4.0 × 10 −6 s −1 , depending on the altitude, for a zenith angle of 50 • .…”
Section: Discussionsupporting
confidence: 80%
“…The resulting peroxy radical INT8, OCC(OO q )COOH, has a fairly mobile hydrogen atom, which can temporarily migrate to the oxygen radical site; this H shift was calculated to be endothermic by only 11 to 12 kcal mol −1 . The resulting hydroperoxide acyloxy radical, OCC(OOH)C(O q )O, is not an energetic minimum at the chosen level of theory, spontaneously reforming the carboxylic acid peroxy radical; this is contrary to similar reactions in aliphatic carboxylic acid atmospheric oxidation where CO 2 is preferentially eliminated (Lockhart et al, 2013;da Silva, 2010). All reactions of the transient hydroperoxide examined, including CO 2 elimination and cyclization, appear to have relatively high barriers exceeding 20 kcal mol −1 relative to the peroxy radical.…”
Section: Theoretical Study Of the Reaction Mechanismmentioning
confidence: 94%
See 1 more Smart Citation
“…In unpolluted regions, with low NOx mixing ratios and high amounts of VOCs glyoxal photolysis may contribute to the regeneration of HOx (HO + HO 2 ) in the troposphere. These conditions occur over tropical rainforests, where high emissions of isoprene may suppress ambient OH levels if recycling mechanisms such as via glyoxal photolysis did not occur . Additionally, glyoxal contributes to the formation of secondary organic aerosol (SOA) and cloud droplets, which in turn affect climate and air quality …”
Section: Introductionmentioning
confidence: 99%
“…Contemporary, other trace gases have been investigated as the results from the isoprene studies show that OH recycling through isoprene-RO 2 , alone, is not sufficient to explain the OH concentrations observed in the field. Chamber and laboratory studies on methacrolein (MACR) Fuchs et al, 2014), methyl vinyl ketone (MVK) (Praske et al, 2015), isoprene hydroxy hydroperoxide (D' Ambro 10 et al, 2017) and glyoxal (Feierabend et al, 2008;Lockhart et al, 2013), important products from the oxidation of isoprene by OH, also have shown new OH recycling paths as predicted by theory (Peeters et al, 2009;da Silva, 2010;Setokuchi, 2011;da Silva, 2012). Further laboratory studies also have discovered OH radical recycling in the bimolecular reaction of HO 2 with acyl peroxy radicals which was previously considered to be a radical termination reaction only Groß et al, 2014;Praske et al, 2015).…”
Section: Introductionmentioning
confidence: 99%